PENTINGNYA KECERDASAN EMOSIONAL DALAM PEMBELAJARAN - Kadeni Kadeni (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
Learning not only as atransfer of knowledge alone but is an activity under taken untu teachers develop the potential of students as a whole to achieve change for the better. Teachers than intellectual understanding must also be able to understand the emotional intelligence of students. Emotional intelligence is the ability to regulate one's emotional life within telligence, emotion and disclosure of maintaining harmony throughself-awareness, self-control, self-motivation, empathy and social skills.                   It must be understood if students only have high academic intelligence, they tend to have an unwarranted sense of restless, overlycritical, fussy, tend to with draw, seemed cool and less likely to express resent mentan danger appropriately if not supported with emotional intelligence, then the people is often asource of problems. Students who have high intelligence but low emotional intelligence level ittends to be seen as a hard-nosed, hard to get along, easily frustrated, do not easily trust others, not sensitive to environmental condition sand tend to despair when experiencing stress. The opposite condition, experienced by those who have the intelligence level of the average but has high emotional intelligence. There fore it is time all the teachers in the learning does not only focus on the intellectual but emotional intelligence of students should be a concern that they can achieve success in living life to come.